PERSPECTIVE DIRECTIONS OF THE FISHING DEVELOPMENT INTERSKO-CASPIAN FISH INDUSTRIAL SUBREGION - A. S. Abdusamadov; P. G. Musayev; O. P. Grigorian; R. M. Barkhalov; E. A. Akhmayev; P. S. Taibov (Юг России: экология, развитие)
Aim. To work out perspective of stable fishing development in Tersko-Caspian fish industrial subregion.Location. Tersko-Caspian subregion.Methods. Analysis of own and literature materials according to the state of reserves and catches of the main food fish species in the region of investigation.Results. Proposals on the main perspective directions of fish industry and also the improvement of thecnoironment of the water biological resources, permilting to increase effectiveness of their natural reproduction of fish are worked out.Main conclusions. In the perspective the organization of sea fishery of common sprat, herrings, grey mullet and aterines in the Russian part of the Middle Caspiy will promote the creation of stable fishery and fish processing production in the region.